Factors associated with mortality, length of hospital stay and diagnosis of COVID-19: Data from a field hospital - Vanessa da Costa Sousa; Mayara Calixto da Silva; Matheus Pereira de Mello; João Antonio Matheus Guimarães; Jamila Alessandra Perini (Elsevier, 2022)
Background: During the pandemic of COVID-19, phylogenetic changes have been observed in the characteristics of the virus, in the diagnosis and treatment of the disease. The clinical course and the severe form of the disease depends on several factors. This study characterized the beginning setting for patient care of COVID-19 in a referral center in one of the main capital cities of Brazil. In addition, were evaluated the factors associated with mortality, length of stay, and diagnostic outcome. Methods: A cross-sectional study was conducted during May 2020 (n = 1100). The association of the variables with outcome was evaluated by a multivariable logistic regression model, using odds ratios (OR) and 95 % confidence intervals (CI). Results: Overall, 76 % of patients were COVID-19 positive, and 70 % were diagnosed by RT-qPCR. The majority were male (56 %), and over 52 years old (74 %), 68 % had hypertension, 44 % had diabetes mellitus, and 32 % were obese. The mean length of stay was 10 ± 8 days, which was higher in the 34 % who died (≥14; OR=2; 95 %CI=1.4-4) and who had hypertension (OR=2; 95 %CI=1.3-3) (P < 0.001). The mean length of stay was also higher (P = 0.008) for those patients with pulmonary impairment ≥ 50 % (10.72 ± 8.24), than those with< 50 % (8.98 ± 6.81). Age (>62 and 65 years) was associated with longer hospitalization (OR=2; 95 %CI=1.4-3) and death (OR=6; 95 %CI=3-11). The time of sample collection for RT-qPCR was different between positive and negative tests (P = 0.001), with the time of 4-10 days showing a greater chance for virus detection (OR=2.9; 95 %CI=1.6-5). Conclusion: Death was associated with age and pulmonary impairment. The length of hospitalization was associated with age, hypertension, pulmonary impairment and death. The time of sample collection to perform RT-qPCR and the rapid test was associated with a positive result for COVID-19. These results highlight the ongoing challenge of diagnosing, treating, and mitigating the effects caused by the COVID-19 pandemic.